2000
DOI: 10.1021/jm000309t
|View full text |Cite
|
Sign up to set email alerts
|

Conformationally Restricted Analogues of 1N,14N-Bisethylhomospermine (BE-4-4-4):  Synthesis and Growth Inhibitory Effects on Human Prostate Cancer Cells

Abstract: Twelve analogues of 1N,14N-bisethylhomospermine (BE-4-4-4) with restricted conformations were synthesized in the search for cancer chemotherapeutic agents with higher cytotoxic activities and lower systemic toxicities than BE-4-4-4. The central butane segment of BE-4-4-4 was replaced with a 1,2-substituted cyclopropane ring, a 1,2-substituted cyclobutane ring, and a 2-butene residue. In each case, the cis/trans-isomeric pair was synthesized. Cis-monounsaturation(s) was also introduced at the outer butane segme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0
1

Year Published

2003
2003
2008
2008

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 23 publications
4
50
0
1
Order By: Relevance
“…Although inhibitors of virtually all of the biosynthetic enzymes in polyamine metabolism have been synthesized, none has demonstrated clinical efficacy as a single agent in clinical trails for cancer (see [20]). In an attempt to overcome the limitations encountered with specific inhibitors of enzyme function, we and others have exploited the self-regulatory properties of polyamine metabolism for therapeutic advantage through the use of structural analogues of the natural polyamines [4,5,8,18,39,43,44,49]. The initial studies with polyamine analogues, particularly with BENSpm, were promising, but clinical trials with a number of analogues in lung, breast, and other tumors did not reveal efficacy as single agents.…”
Section: Discussionmentioning
confidence: 99%
“…Although inhibitors of virtually all of the biosynthetic enzymes in polyamine metabolism have been synthesized, none has demonstrated clinical efficacy as a single agent in clinical trails for cancer (see [20]). In an attempt to overcome the limitations encountered with specific inhibitors of enzyme function, we and others have exploited the self-regulatory properties of polyamine metabolism for therapeutic advantage through the use of structural analogues of the natural polyamines [4,5,8,18,39,43,44,49]. The initial studies with polyamine analogues, particularly with BENSpm, were promising, but clinical trials with a number of analogues in lung, breast, and other tumors did not reveal efficacy as single agents.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this success, novel combination therapies with bortezomib are being tested for efficacy and for their potential in circumventing drug resistance in MM. CGC-11093 is a novel polyamine analogue that has completed a phase I trial for the treatment of cancer (14,15). Given the important role of polyamines in pathways targeted by the mechanism of action of bortezomib, we hypothesized that CGC-11093 may enhance its therapeutic efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that CGC-11047 is more effective in prevention than in curing an established infection, which we propose is due to the ability of this group of analogues to upregulate host cell SSAT, resulting in the overproduction of acetylated polyamines (17) and their resultant excretion into the lumen of the gut from where it is voided, making it unavailable to the parasite. By comparison, the 4-4-4 analogues such as CGC-11157 do not induce host cell SSAT (18,27), and their effect is directly on the parasite SSAT, confirming previous studies that demonstrated that parasite SSAT is significantly inhibited by this group of inhibitors (36). Our results of SSAT activity in control and CGC-11157-treated mouse intestinal tissues agree with previous results demonstrating that SSAT activity does not change with exposure to this compound (Table 5).…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of oligoamines was carried out as described previously. Briefly, N 1 -monoethyl tetramides in which the amino groups were protected by a mesitylenesulfonyl residue (18,27) were dimerized by reactions with (E)-or (Z)-2-butene-1,4-diyl-bis(mesitylenesulfonate) to give the corresponding octamide. The protecting group was then removed, and the oligoamine was isolated as the hydrochloride.…”
Section: Prevention Studiesmentioning
confidence: 99%